Adherence and retention to the self-managed community-based Step Into Health program in Qatar (2012–2019) - Chrismas, Bryna C. R.; Majed, Lina; Al-Mohannadi, Abdulla Saeed; Sayegh, Suzan (Frontiers in Public Health, 2022)
Purpose: Investigate adherence and retention to the ‘Step into Health (SIH)’ initiative (www.stepintohealth.qa), a Qatari (2012-2019) self-managed community-based health program Methods: Participants (16,711; 16 - 80 years; 37% females, 34% Qatari) used a pedometer or smartphone application (app) to measure step count. Absolute adherence (ADH) and retention (RET) were calculated, with ADH (%) the ratio between number of days data and SIH enrollment length (RET). Linear Mixed Models identified differences in ADH between RET groups, main effects (i.e. sex, device, age, BMI, nationality) and interaction effects for ADH (RET entered as a covariate). Results: Average ADH and RET to SIH (irrespective of sex, age, device and BMI) was 50% (± 31%), and 16% (± 20%) respectively, with ADH differing significantly between RET groups (F = 460.2, p < 0.001). RET (as a covariate) revealed a significant main effect for device (F = 12.00, p < 0.001) and age (F = 4.31, p = 0.001) on ADH observed. There was a significant association between RET and sex (p < 0.001), device (p < 0.001), and age groups 16 – 25 y (p < 0.001), and 26 – 35 y (p < 0.001). There were no significant main effects for sex or BMI on ADH, and no interaction effects (p ≥ 0.21) observed. Conclusions: Follow-up data (e.g. interviews, focus groups, etc.) determining why differences in ADH and RET are observed appears prudent. To convert those that lapsed and/or abandoned SIH/PA into committed long-term PA adherers. This would be a first step to develop targeted public health promotions and initiatives to enhance health outcomes at a population level.